Challenges and Strategies in Engaging Adult Learners in the face-to-face facilitation in ODL - Wardah Mohamad; Zulaika Zakariah; Ratna Khuzaimah Mohamad; Liana Mohamad (2014)
Engaging students in the classroom have become more crucial in education as the attention span of students remain the same despite the increase in learning hours. Many studies have been done on this especially at the primary and secondary level. However, there are less studies being done at the tertiary level of education. With the advancement of technology and the recent increase in distance learning and on-line learning, the number of hours dedicated to face-to-face teaching has been reduced. This means that learners have to absorb the same amount of knowledge in lesser number of hours. This study is a conceptual paper based on a literature review which focuses on how academicians can engage learners through various creative and innovative solutions. It identifies the challenges faced by academicians in teaching adult learners and explores avenues that can be pursued to engage these learners. At the end of the paper, strategies that have been successfully implemented in OUM Business School are documented as a basis for future research efforts. It was concluded that all tutors and facilitators should be committed to the development of innovation and creativity in the learning environment in order to engage learners in the classroom. This would ensure that quality in teaching and learning is achieved.